OPTIMALISASI DESAIN PASAR TRADISIONAL: STUDI KASUS PERMASALAHAN SIRKULASI PENGGUNA PASAR SEGAMAS PURBALINGGA - Naufal Kresna Diwangkara; Fahrul Al Rasyid; Gunawan Surya Damara; Nova Setyaningsih; Rizqi Ariestya Martiano; Tirta Yoga Saputra (Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2025)
This study investigates the main issues faced by the Segamas Traditional Market in Purbalingga. This research focuses on visitor circulation and the layout of trading zones that do not meet the standards of a traditional market. Data were obtained through field observations, interviews, and documentation using a qualitative descriptive approach based on case studies. The research results show that narrow circulation paths, unorganized vendor zoning, and a lack of supporting facilities hinder economic activities and visitor comfort. The spatial design approach offered by the researchers includes dividing the market into three main categories: dry zone, semi-dry zone, and wet zone, based on the nature of the commodities. Additionally, technical recommendations are formulated by considering SNI standards and national regulations regarding traditional markets. The redesign of the market block is carried out to improve space efficiency, make the buildings more viable, and enhance the market's function as a sustainable local economic center. This research contributes to the discussion on the revitalization of traditional markets, relying on adaptive public policies and participatory spatial planning principles.